(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The paper considers the organization of the use of circular training to improve the technical, tactical and functional training of young athletes, to reveal the basic theoretical and organizational and methodological principles of using the circular training method in the educational and training process, to improve the functional abilities of basketball players, to substantiate the structure and content of the proposed methodology of circular training of basketball players. The main organizational and methodological directions of building a circular training are allocated (Extensive variant of circular training, this method involves performing a series of exercises alternating with short breaks, which allows you to actively involve different muscle groups without significantly increasing the load on individual muscle groups, this variant is focused on improving aerobic performance, which is important for basketball players, since the game requires prolonged physical activity. The training can be organized for both group and individual work. The use of extensive circular training in the training process contributes to the development of endurance, strength and agility, this training can be carried out in a short time, combines various physical exercises and supports the motivation of athletes; Intensive tempo version of circular training is the most effective for the development of physical qualities of athletes. This approach focuses on performing physical exercises with high intensity and short breaks, which maximizes the level of physical endurance. In this training, exercise sets are performed with maximum intensity, which improves aerobic performance. The use of an intensive tempo variant in the training process helps to increase the overall endurance of athletes, the intensity of training allows you to burn more calories in a short period of time, constant cardio exercise improves blood circulation, such training cannot be monotonous; Intensive interval training is one of the most effective methods of training basketball players. This approach combines short intense activity with periods of rest or less intense loads (split), which allows for maximum stimulation of athletes’ physical capabilities).